2012
DOI: 10.1111/j.1662-6370.2012.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organisational attributes on political participation: results of a multi‐level survey from Switzerland

Abstract: The notion of civil society associations as schools of democracy has resulted in models of political participation that place an emphasis on membership in civic associations as a means of developing personal skills that are conducive to political participation. These suppositions seem well established. It is still contested, however, to what extent the particular characteristics of the associations that offer such membership have an impact on civic engagement. Expanding recent research that mainly builds on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
11
0
1
Order By: Relevance
“…This result is consistent with previous findings, although the wording of the question items is not identical (Armingeon ; Bäck et al. ; Schulz and Bailer ). These two dimensions employed separate participation indices using the factor scores as dependent variables; the two dimensions are labeled as contact and protest (see Table ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with previous findings, although the wording of the question items is not identical (Armingeon ; Bäck et al. ; Schulz and Bailer ). These two dimensions employed separate participation indices using the factor scores as dependent variables; the two dimensions are labeled as contact and protest (see Table ).…”
Section: Resultssupporting
confidence: 93%
“…The analysis reveals two main factors of participation among the items in the survey: contact and protest (see the appendix for the question wording). This result is consistent with previous findings, although the wording of the question items is not identical (Armingeon 2007;B€ ack et al 2011;Schulz and Bailer 2012). These two dimensions employed separate participation indices using the factor scores as dependent variables; the two dimensions are labeled as contact and protest (see Table 1).…”
Section: Resultssupporting
confidence: 89%
“…Several studies have investigated the role of civil society at the local level (Schulz and Bailer 2012;Ö berg and Svensson 2012;Varda 2012). Studies have also underlined the importance of the political context when analyzing the consequences of civic engagement and have shown that the attitudes of local political elites influence how citizens' activities are received (Oxendine et al 2007).…”
Section: The Importance Of the Institutional Contextmentioning
confidence: 99%
“…Scholars have looked for relationships between associational involvement and a range of political outcomes, including involvement in political discussions (Wollebaek and Selle 2002), political interest (Bekkers 2005;Halpern 2005;Van Deth 2006;Quintelier 2013), political efficacy (Myrberg 2011) and-ultimatelypolitical action (Van der Meer andVan Ingen 2009;Schulz and Bailer 2012). We examine these four indicators, although we do not expect these socialization effects to be equally strong.…”
mentioning
confidence: 99%